Aerobic granular sludge contains Hyaluronic acid-like and sulfated glycosaminoglycans-like polymers. (1st February 2020) - Felz, Simon; Neu, Thomas R.; van Loosdrecht, Mark C.M.; Lin, Yuemei
Abstract: Glycosaminoglycans (GAGs) are linear heteropolysaccharides containing a derivative of an amino sugar. The possibility of the presence of GAGs in aerobic granular sludge was studied by combining SDS-PAGE with Alcian Blue staining (at pH 2.5 and 1), FTIR, mammalian Hyaluronic acid and sulfated GAG analysis kits, enzymatic digestion and specific in situ visualization by Heparin Red and lectin staining. GAGs, including Hyaluronic acid-like and sulfated GAGs-like polymers were found in aerobic granular sludge. The sulfated GAGs-like polymers contained Chondroitin sulfate and Heparan sulfate/Heparin based on their sensitivity to the digestion by Chondroitinase ABC and Heparinase I & III. Heparin Red and lectin staining demonstrated that, the sulfated GAGs-like polymers were not only present in the extracellular matrix, but also filled in the space between the cells inside the microcolonies. The GAGs-like polymers in aerobic granules were different from those produced by pathogenic bacteria but resemble those produced by vertebrates. Findings reported here and in previous studies on granular sludge described in literature indicate that GAGs-like polymers might be widespread in granular sludge/biofilm and contribute to the stability of these systems. The extracellular polymeric substances (EPS) in granular sludge/biofilm are far more complicated than they are currently appreciated. Integrated and multidisciplinary analyses are significantly required to study the EPS. Graphical abstract: Image 1 Highlights: The EPS in granular sludge/biofilms are far more complicated than they are currently appreciated. Sulfated glycosaminoglycans-like compounds are part of aerobic granular sludge EPS. Hyaluronic acid-like polymers are present in aerobic granular sludge.